Corneal Spherical Aberration and Corneal Asphericity after Small Incision Lenticule Extraction and Femtosecond Laser-Assisted LASIK - Hui Zhang; Yan Wang; Hua Li (Journal of Ophthalmology)
Purpose. To investigate corneal spherical aberration and corneal asphericity after small incision lenticule extraction (SMILE) and femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK). Methods. This study enrolled 70 patients having SMILE and 64 subjects receiving FS-LASIK. The preoperative spherical equivalent (SE) was −5.83 ± 1.23 diopters (D) and −6.20 ± 1.52 D, respectively. The uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), SE, corneal spherical aberration, and asphericity over the 6.0 mm cornea were evaluated preoperatively and postoperatively. Results. At 6 months, the UDVA, CDVA, and SE were −0.12 ± 0.11, −0.05 ± 0.05, and −0.16 ± 0.19 D in SMILE and −0.10 ± 0.06, −0.03 ± 0.06, and −0.08 ± 0.25 D in FS-LASIK. There was no difference between groups in the postoperative UDVA, CDVA, or SE (P>0.05). SMILE showed lower inductions of spherical aberration along the anterior surface and the total cornea and less increases in corneal asphericity of the anterior surface postoperatively than FS-LASIK (P<0.01). There were significant correlations between the changes in spherical aberration and corneal asphericity (P<0.001). Conclusions. SMILE and FS-LASIK exhibited excellent visual results and refractive outcomes. SMILE induced less increase in corneal spherical aberration and better preserved the corneal asphericity of the anterior corneal surface than FS-LASIK. Corneal asphericity changes contributed to the corneal spherical aberration changes following SMILE and FS-LASIK.